FAKTOR-FAKTOR MENENTUKAN DALAM KEBERHASILAN OPTIMALISASI PENGELOLAAN PENERIMAAN NEGARA DI SEKTOR KELAUTAN DAN PERIKANAN - Dida Daniarsyah (Jurnal Administrasi Publik, 2016)
Changes in the global order and national economic, social, political and technological dynamic growing demand accelerated national development in various sectors. No exception marine and fisheries sector. These sectors need to adapt and meet the challenges of the strategic environment that moves fast.The magnitude of the potential for marine resources and fisheries are not yet able to contribute significantly to the income or revenues in the marine and fisheries sector so that the implications of fishing communities in particular and citizens in general have not increased the level of welfare. This shows riweuhnya problems. One kariweuhan the problem, not optimal or poor management of state revenue in the sector and Fisheries.Potential state income or non-tax revenues (non-tax), which can be optimized in the marine and fisheries sector that has not been excavated and managed in an orderly manner will be successfully optimized the concept of normative and academic as well as the deciding factor is the Leader and Leadership, Civil Society / Community Activist Fishing organized, Institutional Reform and human Resources, Technology Adoption, Creation mision values and share a culture of honesty, collaboration between agencies, communication via medsos.Optimization of state revenue in the marine and fisheries sector ranging from Rp25 trillion per year that can be imposed on ships over 30 GT bertonasi because the ship will be able to catch fish at sea about 2000 tons of various levies such as taxes and other fisheries exploitation can be optimized. And the potential of the catch wholly revolves around Rp300 trillion each year. Export potential of fish farming sector will contribute about 60 million tonnes per year.